Rugby talent development - Worsnop, S. A. (International Sport Coaching Journal, 2016)
The purpose of this article is to examine the application of talent development principles to the coaching of rugby. It will consider the generic and sport specific problems of talent identification and selection, particularly the danger of early selection that poses the dual problems of early disengagement on the one hand and over specialization on the other. The paper will touch upon the various proposed models of athlete development and discuss the ways in which a national governing body of sport can influence player development along the age continuum. The role of the individual coach in developing young players and the importance of coach development and education will also be considered. Understanding the needs of players at different times in their development, and having a clear knowledge of how to improve performance in an efficient, time restrained but also enjoyable manner is a key skill for any coach. However, this skill requires time to grow and many coach education systems do not provide the ongoing support mechanisms that will enable a coach to grow and flourish, resulting in a less than optimal coaching environment.